Three new species of Karwinskia (Rhamnaceae) from Mexico - Fernández Nava, Rafael (Instituto de Ecología, A.C., 1988)
Three new species of Karwinskia (Rhamnaceae) are described from Mexico: K. johnstonii from Michoacán, K. rzedowskii from S of Durango, Jalisco and SW of Zacatecas and K. venturae from the State of Mexico and Guerrero.